Challenges for NGOs Partnering with Corporations: WWF Netherlands and the Environmental Defense Fund. (1st February 2011) - van Huijstee, Mariette; Pollock, Leo; Glasbergen, Pieter; Leroy, Pieter
Abstract : As the market and civil society sectors reflect different core logics, non-governmental organisations (NGOs) that partner with companies need strategies to cope with these differences. This paper seeks to provide insight into the coping strategies of environmental NGOs that partner with corporations. We present an assessment framework to analyse the strategies of the Environmental Defense Fund and the World Wildlife Fund for Nature Netherlands as case studies. The analysis demonstrates that the strategic options for a partnering NGO are guided and constrained by the choices the NGO makes with regard to its action strategy towards companies. Although individual NGOs manage to cope adequately with the challenges that the partnership trend poses to their organisations, we argue that the partnering trend also creates challenges for the NGO field as a whole.